Efektifitas Penggunaan Virgin Coconut Oil (VCO) Terhadap Pencegahan Diaper Rash pada Bayi Usia 1-12 Bulan di Wilayah Kerja Puskesmas Depok II Sleman - Jennifa Jennifa; Atik Ba'diah; Eni Purwaningsih (LPPM STIKES Guna Bangsa, 2014)
Background : Diaper rash is a dermatitis eclusively localized in the diaper area, commonly attack children less than 2 years of age, usually conservatively cured by the parents so that only 7-35% babies suffer from diaper rash. Virgin Coconut Oil (VCO) that are beneficial to health, has been widely sought after to resolve health problems, also acts against bacteria and microbe. The Content of Medium Chain Triglycerides (MCT) in VCO hydrolyzed faster, and more quickly absorbed in the body tissue. Aim :The aim of this research is to determine the effect of Virgin Coconut Oil on prevention diaper rash. Methods : This research is pre-experimental with posttest only design. Conducted from May to June 2014. The research was done in Puskesmas Depok II Sleman area, with 14 respondents according to the determined criteria. Respondents were instructed to apply VCO in the diaper area once every morning after bath for 30 days. Data analysis used univariable analysis, bivariable analysis with Chi-Square test. Result :The results of the data obtained in this study was 78.6% of respondents regularly use VCO, but not experiencing diaper rash and there are 21.4% of respondents do not regularly use VCO and 14.3% had diaper rash. The results showed there was significant effect of VCO on prevention diaper rash with a significance p value = 0,003(p<0,05). Conclusion : Therefore it can be concluded that applying of VCO has a significant effective on prevention diaper rash. The use of VCO one time in the morning after a shower made ​​for ≥21 days was more effective against the prevention of diaper rash compared with the use of VCO <21 days.